On the design and characterization of femtoampere current-mode circuits. - Linares-Barranco, B.
In this paper, we show and validate a reliable circuit design technique based on source voltage shifting for current-mode signal processing down to femtoamperes. The technique involves specific-current extractors and logarithmic current splitters for obtaining on-chip subpicoampere currents. It also uses a special on-chip sawtooth oscillator to monitor and measure currents down to a few femtoamperes. This way, subpicoampere currents are characterized without driving them off chip and requiring expensive instrumentation with complicated low leakage setups. A special current mirror is also introduced for reliably replicating such low currents. As an example, a simple log-domain first-order low-pass filter is implemented that uses a 100-fF capacitor and a 3.5-fA bias current to achieve a cutoff frequency of 0.5 Hz. A technique for characterizing noise at these currents is also described and verified. Finally, transistor mismatch measurements are provided and discussed. Experimental measurements are shown throughout the paper, obtained from prototypes fabricated in the AMS 0.35-μm three-metal two-poly standard CMOS process.
Keywords: 0.35 micron; 0.5 Hz; 100 fF; 3.5 fA; Current mirror; Current-mode signal processing; Cutoff frequency; Femtoampere current-mode circuits; Leakage setups; Log-domain first-order low-pass filter; Logarithmic current splitters; On-chip sawtooth oscillator; On-chip subpicoampere currents; Source voltage shifting; Specific-current extractors; Three-metal two-poly standard CMOS; Transistor mismatch